MCO1 and MCO3, two putative ascorbate oxidases with ferroxidase activity, new candidates for the regulation of apoplastic iron excess in Arabidopsis. (16th November 2022) - Brun, Alexis; Smokvarska, Marija; Wei, Lili; Chay, Sandrine; Curie, Catherine; Mari, Stéphane
Abstract: Iron (Fe) is an essential metal ion that plays a major role as a cofactor in many biological processes. The balance between the Fe 2+ and Fe 3+ forms is central for cellular Fe homeostasis because it regulates its transport, utilization, and storage. Contrary to Fe 3+ reduction that is crucial for Fe uptake by roots in deficiency conditions, ferroxidation has been much less studied. In this work, we have focused on the molecular characterization of two members of the MultiCopper Oxidase family (MCO1 and MCO3) that share high identity with the Saccharomyces cerevisiae ferroxidase Fet3. The heterologous expression of MCO1 and MCO3 restored the growth of the yeast fet3fet4 mutant, impaired in high and low affinity Fe uptake and otherwise unable to grow in Fe deficient media, suggesting that MCO1 and MCO3 were functional ferroxidases. The ferroxidase enzymatic activity of MCO3 was further confirmed by the measurement of Fe 2+ ‐dependent oxygen consumption, because ferroxidases use oxygen as electron acceptor to generate water molecules. In planta, the expression of MCO1 and MCO3 was induced by increasing Fe concentrations in the medium. Promoter‐GUS reporter lines showed that MCO1 and MCO3 were mostly expressed in shoots and histochemical analyses further showed that both promoters were highly active in mesophyll cells. Transient expression of MCO1‐RFP and MCO3‐RFP in tobacco leaves revealed that both proteins were localized in the apoplast. Moreover, cell plasmolysis experiments showed that MCO1 remained closely associated to the plasma membrane whereas MCO3 filled the entire apoplast compartment. Although the four knock out mutant lines isolated ( mco1‐1, mco1‐2, mco3‐1, and mco3‐2 ) did not display any macroscopic phenotype, histochemical staining of Fe with the Perls/DAB procedure revealed that mesophyll cells of all four mutants overaccumulated Fe inside the cells in Fe‐rich structures in the chloroplasts, compared with wild‐type. These results suggested that the regulation of Fe transport in mesophyll cells had been disturbed in the mutants, in both standard condition and Fe excess. Taken together, our findings strongly suggest that MCO1 and MCO3 participate in the control of Fe transport in the mesophyll cells, most likely by displacing the Fe 2+ /Fe 3+ balance toward Fe 3+ in the apoplast and therefore limiting the accumulation of Fe 2+, which is more mobile and prone to be transported across the plasma membrane.